دور التسويق الداخلي في تعزيز الإنتماء التنظيمي بالمؤسسة الإقتصادية دراسة حالة مؤسسة إتصالات الجزائر بالوادي - سارة, سليماني; روميسة, شنوف (University of eloued جامعة الوادي, 2021)
"تهدف هذه الدراسة إلى إبراز دور التسويق الداخلي في تعزيز الانتماء التنظيمي للعاملين، من خلال التطرق للمفاهيم للتسويق الداخلي والانتماء التنظيمي للعاملين، والعلاقة بينهما. وللإجابة على الاشكالية الرئيسية: ""كيف يساهم التسويق الداخلي من خلال أبعاده (التدريب، التمكين والدعم الاداري التحفيز، فرق العمل والاتصال الداخلي في تعزيز الانتماء التنظيمي للعاملين بمؤسسة اتصالات الجزائر بالوادي؟"" اتبعنا المنهج الوصفي التحليلي في الجانب النظري، أما الجانب التطبيقي فقد اعتمدنا على منهج دراسة الحالة، حيث تم اسقاط المفاهيم النظرية على مؤسسة اتصالات الجزائر بالوادي. وكأداة رئيسية للدراسة اعتمدنا على الاستبيان، حيث تم توزيع هذا الاستبيان عشوائيا على عينة من الموظفين مكونة من (45) موظفا، بهدف جمع البيانات فضلا على المقابلات الشخصية، الملاحظة الميدانية والوثائق . وبعد حصر وتجميع البيانات ثم تفريغها وتحليلها باستخدام برنامج SPSS وتم الوصول إلى أن هناك أثر ذو دلالة إحصائية للتسويق الداخلي على الانتماء التنظيمي للعاملين مؤسسة اتصالات الجزائر بالوادي، من خلال أبعاده المتمثلة في التدريب، التمكين والدعم الاداري التحفيز، فرق العمل والاتصال الداخلي) عند مستوى دلالة (0.05≤ a ) ""This study aims to highlight the role of internal marketing in enhancing the organizational affiliation of employees, by addressing the concepts of internal marketing and organizational affiliation of employees, and the relationship between them, to answer the main problem:""How does internal marketing, through its dimensions (training, empowerment, administrative support, motivation, work teams and internal communication) contribute to enhancing the organizational affiliation of Algeria Telecom employees in the valley?"" We followed the descriptive-analytical approach in the theoretical aspect, and on the practical side, we relied on the case study approach, where the theoretical concepts were dropped on the Algeria Telecom Corporation in the valley. As a main tool for the study, we relied on the questionnaire. This questionnaire was randomly distributed to a sample of employees consisting of (45) employees, with the aim of collecting data as well as personal interviews, field observations and documents. After collecting and collecting the data, it was unloaded and analyzed using SPSS. It was found that there is a statistically significant effect of internal marketing on the organizational affiliation of the employees of Algeria Telecom in the valley, through its dimensions of (training, empowerment, administrative support, motivation, work teams and internal communication) at the level of significance α0.05 ≥ "
ماستر ادارة اعمال
Keywords: تسويق داخلی، انتماء تنظيمي، مؤسسة اتصالات الجزائر بالوادي.; marketing, organizational affiliation, Algeria Telecom in El Oued